2014
DOI: 10.1111/jcpt.12131
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the effectiveness of smoking cessation interventions in community pharmacy

Abstract: Pharmacist-led interventions can significantly impact abstinence rates in smokers. Health policymakers should direct incentives for community pharmacists to provide such services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 40 publications
3
84
1
1
Order By: Relevance
“…[18][19][20][21][22][23][24][25] It also builds on existing knowledge of public trust in pharmacists more widely, as evidenced in narrative and systematic reviews of pharmacy based public health activities. [10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25] It also builds on existing knowledge of public trust in pharmacists more widely, as evidenced in narrative and systematic reviews of pharmacy based public health activities. [10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…3 One in 20 deaths in Scotland is attributable to alcohol 4 , with estimates of the total personal, social and economic cost of alcohol in Scotland equating to £7.5 billion per year. 5 The contribution of community pharmacy to public health has been recognised and valued for many years by policy makers and the public [6][7][8][9] with evidence of benefit in smoking cessation, 10 This study aimed to determine the Scottish general public's views regarding the role and involvement of community pharmacists in reducing alcohol consumption amongst customers and alcohol-related harm.…”
Section: Introductionmentioning
confidence: 99%
“…8 11) Still another study reported that the patient group with higher frequency of intervention showed signiˆcantly greater improvement in the cessation rate. 12) A systematic review 13) and meta-analysis 14) that examined articles on smoking cessation guidance by pharmacists also suggested that such guidance was eŠective. In Japan, the Hanamaki Pharmacists Association reported a successful case of cessation guidance using Nicorette .…”
Section: Intoductionmentioning
confidence: 99%
“…Tobacco cessation services which included individualized counseling or within-group sessions have resulted in better smoking abstinence as compared with usual care. Abstinence has been either self-reported or biochemically verified using exhaled carbon monoxide, salivary or urinary cotinine levels [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%